2021
DOI: 10.1007/s11357-021-00362-w
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of the heat shock axis during exceptional longevity in Ames dwarf mice

Abstract: How the heat shock axis, repair pathways, and proteostasis impact the rate of aging is not fully understood. Recent reports indicate that normal aging leads to a 50% change in several regulatory elements of the heat shock axis. Most notably is the age-dependent enhancement of inhibitory signals associated with accumulated heat shock proteins and hyper-acetylation associated with marked attenuation of heat shock factor 1 (HSF1)–DNA binding activity. Because exceptional longevity is associated with increased res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 80 publications
(95 reference statements)
0
13
2
Order By: Relevance
“…Consistent with other studies on aging and other tissue, HSF1 -DNA binding levels in brain from older mice decrease from 30 to 50% relative to brains from younger mice (3M). Unlike other studies, however, we nd that the age -dependent decline in brain HSF1 -DNA binding occurs at the 12M juncture rather than the 20-24M period of time in other mouse tissue [Trivedi et al 2021]. By contrast, brain samples from long lived Dwarf mice demonstrate a steady increase in HSF1-DNA binding over the life span with most robust levels of HSF1 -DNA binding observed in the 22M when compared to 3M brains.…”
Section: Discussioncontrasting
confidence: 91%
“…Consistent with other studies on aging and other tissue, HSF1 -DNA binding levels in brain from older mice decrease from 30 to 50% relative to brains from younger mice (3M). Unlike other studies, however, we nd that the age -dependent decline in brain HSF1 -DNA binding occurs at the 12M juncture rather than the 20-24M period of time in other mouse tissue [Trivedi et al 2021]. By contrast, brain samples from long lived Dwarf mice demonstrate a steady increase in HSF1-DNA binding over the life span with most robust levels of HSF1 -DNA binding observed in the 22M when compared to 3M brains.…”
Section: Discussioncontrasting
confidence: 91%
“…Mammalian aging correlates with proteostatic collapse, including compromised molecular chaperone levels and functions 16 , 17 , 53 55 . Since cellular senescence is a crucial biological process underlying aging 56 , we investigated whether below threshold levels of Hsp90 trigger accelerated senescence.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude from this series of experiments that mammalian organisms and cells that cannot fine-tune Hsp90 to the physiologically required levels might experience accelerated aging and premature death, such as those 90αKO 90βHET embryos, which fail to increase Hsp90β levels. Several molecular chaperones, including Hsp90, are known to be reduced during aging in mammals, including in humans 53 55 . We found that the mTOR inhibitor and anti-aging drug rapamycin 57 , 58 reduces the heat stress-induced senescence marker p21 in Hsp90α/β KO HEK293T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the loss of HSF-DNA binding with usual aging and its gain during exceptional aging (Jurivich et al 2020 ; Trivedi et al 2021 ) we examined HSF1 protein and mRNA levels between the two aging groups of mice. Figure 1 D shows that HSF1 protein levels at 3 M steadily decline in 12 M and 22 M old wild type brain by 47% and another 9% respectively (p = 0.005 for 3 vs 12 M and p = 0.5029 for 12 vs 22 M).…”
Section: Resultsmentioning
confidence: 99%